The Tradition of Using Banjar Malay Language in Learning Classical Islamic Texts within Islamic Boarding Schools in South Kalimantan - Mukhlis Mukhlis; Zulfa Jamalie (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
This study examines the tradition of using Banjar Malay language in learning kitab turats within Islamic boarding schools (pesantren) in South Kalimantan. The objective of this research is to explore how the use of local language contributes to students’ understanding of classical Islamic texts as well as its role in preserving local cultural identity. The study employs a qualitative approach using library research methods by analyzing relevant books, journals, and academic literature related to pesantren education, sociolinguistics, and Islamic pedagogy. The findings indicate that Banjar Malay language functions as an effective pedagogical bridge that simplifies complex Arabic texts and enhances students’ comprehension. In addition, its use strengthens emotional relationships between teachers and students, increases classroom participation, and supports the transmission of local cultural values. The tradition also plays a significant role in maintaining regional linguistic identity amid modernization and globalization. Therefore, the integration of Banjar Malay language in pesantren learning represents a form of culturally responsive Islamic education that is both adaptive and preservative in nature